Antibacterial activity of Lactobacillus plantarum bacteriocin as a dermal probiotic against Pseudomonas aeruginosa isolated from diabetic foot ulcer - Haneen Majid Abdulkareem Al-Asadi; Khalid Jaber Kadhum Luti (Journal of Madenat Alelem University College, 2023)
The current study was considered to select a appropriate isolate of Lactobacillus sp. in order to use it as an antibacterial formula for treating diabetic foot ulcer disease in diabetic mellitus patients, over two hundred Lactobacillus isolates were collected from different sources for this purpose  and subjected to a screening program to evaluate their antagonism activities against multi-drug resistant (Pseudomonas aeruginosa ) foot ulcer pathogen which were chosen from one hundred and twenty pathogenic isolates. several Lactobacillus isolates were selected after primary and secondary screening according to their ability to inhibit the growth of P. aeruginosa and ability to produce bacteriocin. Results showed the isolate Lactobacillus L40 was selected as a highest bacteriocin producing isolate which was further characterized as Lactobacillus plantarum through Vitek 2 system. Bacteriocin from L. plantarum L40 was partially purified by precipitation with ammonium sulphate with 80% saturation and then separated with sephadex G-150 gel filtration. The specific activity of the resulted partial purified bacteriocin was increased to 864.86 AU/mg with 13-fold purification and 64% yield. The study of bacteriocin characterization revealed that the activity of bacteriocin was stable after 10 min at 20, 30, 40C° whereas, more than 50% of the bacteriocin activity was lost after exposure to 50C° and decreased to approximately 20 AU/ml at 60,70 and 80C°. In addition, bacteriocin activity showed stability at pH 6 and 7 for 30 min while, it was decreased by approximately 50% at pH 5 and 8, and completely inhibited at pH 4 and 9. Antimicrobial activity tests of the partial purified bacteriocin against P. aeruginosa clinical isolates showed that bacteriocin was active against Gram negative bacteria. Formula was selected and optimized that can be used in this study, formula containing bacteriocin produced by L. plantarum L40 formula showed antibacterial activity by inhibiting (P. aeruginosa) growth. The results showed the possibility of using partially purified bacteriocin from L. plantarum L40 as an effective probiotic to deal with some skin pathogens, and treat skin diseases such as diabetic foot ulcer disease. The results supported the idea of using probiotic as an alternative method for the treatment with antibiotics.